Rapid and simple analysis of short and long sequencing reads using DuesselporeTM - Vogeley, Christian; Nguyen, Thach; Woeste, Selina; Krutmann, Jean; Haarmann-Stemmann, Thomas; Rossi, Andrea (Frontiers in Genetics, 2022)
Transcriptome analysis experiments enable researchers to gain extensive insights into the molecular mechanisms underlying cell physiology and disease. Oxford Nanopore Technologies (ONT) has recently been developed as a fast, miniaturized, portable, and a cost effective alternative to Next Generation Sequencing (NGS). However, RNA-Seq data analysis software that exploits ONT portability and allows scientists to easily analyze ONT data everywhere without bioinformatics expertise is not widely available. We developed DuesselporeTM, an easy-to-follow deep sequencing workflow that runs as a local webserver and allows the analysis of ONT data everywhere without requiring additional bioinformatics tools or internet connection. DuesselporeTM output includes differentially expressed genes and further downstream analyses, such as variance heatmap, disease and gene ontology plots, gene concept network plots, and exports customized pathways for different cellular processes. We validated DuesselporeTM by analyzing the transcriptomic changes induced by PCB126, a dioxin-like PCB and a potent aryl hydrocarbon receptor (AhR) agonist in human HaCaT keratinocytes, a well characterized model system. DuesselporeTM was specifically developed to analyze ONT data, but we also implemented NGS data analysis. DuesselporeTM is compatible with Linux, Microsoft, and Mac operating systems, and allows convenient, reliable, and cost-effective analysis of ONT and NGS data.